Contemporary Second Language Assessment : Contemporary Applied Linguistics Volume 4. - Wei, Li (Contemporary applied linguistics., 2016)
"Contemporary Second Language Assessment includes chapters on key aspects of second language assessment such as test construct, diagnosis, exam design, and the growing range of public policy, social and ethical issues. Each of the contributors is an expert in their area; some are established names while others are talented newcomers to the field. The chapters present new research or perspectives on traditional concerns such as test quality; fairness and bias; the testing of different language skills; the needs of different groups of examinees, including English language learners who need to take content tests in English; and the use of language assessments for gate-keeping purposes. The volume demonstrates how language assessment is informed by and engages with neighbouring areas of applied linguistics such as technology and language corpora. The book represents the best of current practice in second language assessment and, as a one volume reference, will be invaluable to students and researchers looking for material that extends their understanding of the field"--